THE EVOLUTION OF THE SOUTHERN MARGIN OF THE EAST EUROPEAN CRATON BASED ON SEISMIC AND POTENTIAL FIELD DATA - Kostyuchenko S.L.; Solodilov L.N.; Vedrentsev A.G.; Popolitov K.E.; Aleshina A.F.; Morozov A.F.; Stephenson R.A.; Vishnevskaya V.S.; Yegorova T.P. (My University, 2004)
This paper presents an integrated geophysical study of the southern margin of the East European Craton (EEC) in the Karpinksy Swell-North Caucasus area. It presents new interpretations of deep refraction and wide-angle reflection “deep seismic sounding” (DSS) data as well as conventional seismic and CDP profiling and new analyses of potential field data, including three-dimensional gravity and magnetic modelling. An integrated model of the physical properties and structure of the Earth's crust and, partially, upper mantle displays distinct features that are related to tectonic history of the study area. The Voronezh Massif (VM), the Ukrainian Shield and Rostov Dome (RD) of the EEC as well as the Donbas Foldbelt (DF), Karpinsky Swell (KS), Scythian Plate (SP) and Precaspian Basin (PCB) constitute the geodynamic ensemble that developed on the southern margin of the continent Baltica. There proposed evolutionary model comprises a stage of rifting during the middle to late Devonian, post-rift extension and subsidence during Carboniferous–early Permian times (synchronous with and related to the southward displacement of the Rostov Dome and extension in a palaeo-Scythian back-arc basin), and subsequent Mesozoic and younger evolution. A pre-Ordovician, possibly Riphean (?), mafic magmatic complex is inferred on a near vertical reflection seismic cross-section through the western portion of the Astrakhan Dome in the southwest part of the Precaspian Basin. This complex combined with evidence of a subducting slab in the upper mantle imply the presence of pre-Ordovician (Riphean?) island arc, with synchronous extension in a Precaspian back-arc basin is suggested. A middle Palaeozoic back-arc basin ensemble in what is now the western Karpinsky Swell was more than 100 km to the south from its present location. The Stavropol High migrated northwards, dislocating and moving fragments of this back-arc basin sometime thereafter. Linear positive magnetic anomalies reflect the position of associated faults, which define the location of the eastern segment of the Karpinsky Swell. These faults, which dip northward, are recognised on crustal DSS profiles crossing the Donbas Foldbelt and Scythian Plate. They are interpreted in terms of compressional tectonics younger than the Hercynian stage of evolution (i.e., post-Palaeozoic).
Keywords: Scythian Plate; Karpinsky Swell; Crustal structure; East European Craton